Pengaruh Media Interaktif Animasi Terhadap Minat Belajar Pada Mata Pelajaran IPA Siswa Kelas IV UPT SDN 066652 Kecamatan Medan Helvetia - Yetty Rosmawati Pangaribuan; Purba, Sondang; Putri Patresia Saragih (Universitas Sari Mutiara Indonesia, 2024)
The aim of this research was to determine the influence of using animated interactive media on students' learning interest in the material I and my needs for class IV UPT SD N 066652 Medan Helvetia. This type of research is quasi-experimental. The population in this study were all fourth grade students at UPT SD Negeri 066652, totaling 46 students. The sampling technique used was a saturated sample. The experimental class consisted of 23 students and the control class consisted of 23 students. The data collection techniques used in this research were questionnaires and documentation. From the results of data analysis, the average post-questionnaire score in the experimental class was 61.48, while the average score in the control class was 52.57. The results of the independent sample test using post-questionnaire data in the experimental and control classes showed a sig (2 tailed) value of 0.005 < 0.05, so Ha was accepted and Ho was rejected. So it can be concluded that animated interactive media has an influence on students' interest in learning science subjects in my material and my needs for class IV UPT SD Negeri 066652 students.